2013
DOI: 10.1111/ap.12020
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention Training for Smoking Cessation in Substance Use Treatment

Abstract: The treatment of nicotine dependence in individuals with substance use disorders has been an area of neglect and contributes to morbidity and mortality. Lack of staff training and education is the most frequently reported barrier to providing smoking cessation treatment in alcohol and other drug (AOD) treatment services. This study assessed the effectiveness of brief intervention training for smoking cessation for staff in AOD treatment services. Participants were recruited from one residential AOD Therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Recent research has determined that lack of staff training and education is the most frequently reported barrier to providing smoking cessation programmes in alcohol and other drug (AOD) services, which include a high proportion of clients with mental health concerns (Daws et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent research has determined that lack of staff training and education is the most frequently reported barrier to providing smoking cessation programmes in alcohol and other drug (AOD) services, which include a high proportion of clients with mental health concerns (Daws et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, integrating smoking cessation treatments into existing mental health care is paramount to reducing smoking rates among individuals with mental health concerns (Prochaska 2011) and points to a critical need to engage and educate MHPs on evidence-based tobacco cessation. Recent research has determined that lack of staff training and education is the most frequently reported barrier to providing smoking cessation programmes in alcohol and other drug (AOD) services, which include a high proportion of clients with mental health concerns (Daws et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Programs that used resources developed by educational institutions or universities [19,25,40] were perceived to be of high credibility by the participants. Although many of the programs were supported by government funding, none of the studies reported specifically applying government guidelines in the development of resources.…”
Section: The Cfir Domain Of Intervention Characteristicsmentioning
confidence: 99%
“…With this in mind, it is of critical importance to stakeholders, such as policymakers and organizational leadership (e.g., center leadership), to understand organizational factors that might affect training effectiveness. Training effectiveness is typically assessed via attendees' knowledge change/gain from pre-to post-training [23,27]. Some organizational factors affecting knowledge change after training have been delineated for behavioral health treatment facilities [28].…”
Section: Introductionmentioning
confidence: 99%
“…The receipt of training on empirically-based methods to address tobacco use disorders has been associated with an increase in the provision of interventions for tobacco-using SUD patients [ 21 , 22 ]. Among SUTCs that have provided tobacco training for their employees, there have been increases in skills, knowledge, confidence, and supportive attitudes regarding concurrent tobacco treatment with SUD treatment as well as decreases in clinical misconceptions [ 7 , 23 ]. Research suggests that increasing knowledge among clinicians is integral to their implementation of tobacco cessation services: when clinicians had more training and were equipped with tobacco treatment skills, they were more likely to implement the five A’s (ask patients about their tobacco use, advise them to quit, assess their willingness to quit, assist them in quitting, and arrange for follow-up); counsel on tobacco cessation; and provide pharmacotherapy to patients when indicated [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%